Theoretical Study of Interatomic Properties of Ruthenium Half-Sandwich Anticancer Complexes Containing Ru-N Bonds - A. Adeniyi, Adebayo; A. Ajibade, Peter (Asian Journal of Chemistry, 2015)
The intramolecular properties of five sets of ruthenium based anticancer complexes have been theoretically studied using DFT method. The results shows that these complexes are thermodynamically stable and the stability is significantly enhanced through the high level of polarizability (POL), charge transfer (CT) and electrostatic (ES) contributions which may contribute to their biological effects. The presence of carboxylic unit is found to enhance the contributions of these factors. The features of the QTAIM bond properties of the ruthenium-ligand bond shows they are non-covalent in nature and the bond properties are not significantly altered by the change in the chemical environment of the complexes from one type to the other. However, the QTAIM atomic properties of ruthenium changed significantly with the changes in the chemical environment of the complexes. The NEDA analysis shows that these types of complexes are predominantly characterized with ligand to metal charge transfer (LMCT).